Feasibility study of 4D-online monitoring of density gradients induced by lung cancer treatment using carbon ions - Reidel, Claire-Anne; Pierobon, Enrico; Horst, Felix; Gesson, Lévana; Paz, Athena; Graeff, Christian; Steinsberger, Timo; Zink, Klemens; Witt, Matthias; Senger, Yannick; Finck, Christian; Vanstalle, Marie; et al. (Frontiers in Oncology, 2025)
Tumor motion is a major challenge for scanned ion-beam therapy. In the case of lung tumors, strong under- and overdosage can be induced due to the high density gradients between the tumor- and bone tissues compared to lung tissues. This work proposes a non-invasive concept for 4D monitoring of high density gradients in carbon ion beam therapy, by detecting charged fragments. The method implements CMOS particle trackers that are used to reconstruct the fragment vertices, which define the emission points of nuclear interactions between the primary carbon ions and the patient tissues. A 3D treatment plan was optimized to deliver 2 Gy to a static spherical target volume. The goodness of the method was assessed by comparing reconstructed vertices measured in two static cases to the ones in a non-compensated moving case with an amplitude of 20 mm. The measurements, performed at the Marburg Ion-Beam Therapy Center (MIT), showed promising results to assess the conformity of the delivered dose. In particular to measure overshoots induced by high density gradients due to motion with 83.0 ± 1.5% and 92.0 ± 1.5% reliability based on the ground truth provided by the time-resolved motor position and depending on the considered volume and the iso-energy layers.